Diagnosis in clinical pastoral counselling: the sanctuary model as theological anthropological framework for spiritual assessment and treatment - Hunt, Sonya; Louw, Daniël (Stellenbosch Theological Journal, 2024)
The article investigates the feasibility of the sanctuary model as a possible theological anthropological framework for diagnostic and treatment purposes in clinical pastoral practice. It is argued that the wilderness tabernacle matched the criteria for qualifying as a prototype sanctuary. The building-sanctuary is viewed as a metaphorical “body” for God’s being present in, and daily engagement with, human beings throughout all life trajectories and painful events. The notion of a spirituality of sanctuary is analogously linked with similar concepts in the human body-sanctuary (soulful embodiment) in accordance with Paul’s sanctuary-related anthropological terminology. Within the framework of sanctuary thinking and the founding of a theological anthropology, indicators for the assessment of a Christian spiritual praxis in clinical environments have been derived, suitable for diagnostic assessments and treatment. It is argued that the identification of possible directives for making a spiritual assessment of a person’s state of well-being (wholeness), could provide a broader platform from which patients can describe and interpret their responses to God within the therapeutic process of pastoral caregiving. In this regard, the praxis of a clinical approach is in fact a prolongation of wisdom counselling within the parameters of the discipline of cura animarum.